Analisis Metode Pembelajaran Pendidikan Agama Islam Berbasis Experiental Learning dalam Meningkatkan Praktik Ibadah Siswa di SMKN 1 Kota Bima - Jasman Jasman; Nasaruddin Nasaruddin; Sri Jamilah (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study examines the implementation of an experiential learning-based Islamic Religious Education learning strategy to improve students’ worship practices at SMKN 1 Kota Bima. The study employed a qualitative descriptive approach, with data collected through interviews, observation, and documentation. The findings show that experiential learning was implemented through David Kolb’s four learning stages: concrete experience through direct worship practice, reflective observation through reflection journals and discussions, abstract conceptualization through the reinforcement of theoretical understanding, and active experimentation through the application of worship practices in new situations. This strategy was also linked to students’ vocational competencies to make Islamic Religious Education learning more contextual and meaningful. The implementation of this strategy was supported by teachers’ competence, school policies, the availability of facilities, and students’ motivation to participate in learning. However, its implementation still faced several obstacles, such as limited instructional time, differences in students’ religious practice backgrounds, and limited supporting facilities. In general, the implementation of experiential learning had a positive impact on improving the quality of worship practices, consistency in worship, and students’ spiritual awareness. Experiential learning has proven effective in connecting theory with real practice, enabling students not only to understand Islamic teachings conceptually but also to internalize them in their daily lives.